Pedicled transverse rectus abdominis myocutaneous flap breast reconstruction: Hospital Kuala Lumpur’s early experience - Anuar, Nur A. A.; Awang, Raflis R.; Khoo, Ee T.; Anthonysamy, Daphne; Darail, Nor A. H.; Emran, Nor A. (International Surgery Journal, 2021)
Background: Breast reconstruction is traditionally performed by the plastic surgeons. In the last four years, we have embarked on autologous breast reconstruction. We conducted a retrospective study to evaluate the complications and cosmetic outcomes of a pedicled transverse rectus abdominis myo-cutaneous (TRAM) flap breast reconstruction. Methods: We enrolled forty-one patients who underwent a TRAM flap reconstructive surgery between January 2016 and January 2020 at the hospital Kuala Lumpur, Malaysia. Thorough retrospective reviews of medical records were performed. Patient’s satisfaction on the cosmetic outcome were assessed with the breast-Q questionnaire. Results: Forty-one patients with a mean age of forty-six years old, had ipsilateral pedicled TRAM breast reconstructions for various breast pathologies including invasive carcinoma (n=31, 75.6%), ductal carcinoma in situ (n=8, 19.5%) and phylloides tumor (n=2, 4.9%). Immediate reconstruction was performed in thirty-nine patients and delayed reconstruction in two patients. Based on The American joint committee on cancer (AJCC) TNM system, the pathologic stages among those patients with breast cancer were 0 (n=8, 20.5%), I (n=3, 7.69%), II (n=9, 23.1%), III (n=18, 46.1%), and IV (n=1, 2.56%). During the mean follow-up of seventeen months, flap and donor site complications were reported in twelve patients (29.3%) and five patients (12.1%) respectively. Nineteen were very satisfied and sixteen were satisfied. Conclusions: Breast reconstruction with a TRAM flap can be safely performed by the oncoplastic breast surgeons with good aesthetic outcomes.